Web-based GIS Decision Support System for Paddy Precision Farming - Che'Ya, Nik Norasma (2010)
Precision farming offers numerous benefits and advantages to the farming community for farm productivity improvement. Previous research has led to the development of the offline based Precision Farmer©. This research extends further than the previous work by developing a Web Paddy GIS. The need for this arises due to limitations of Precision Farmer© such as portability, offline system accessibility and affordability by the end users which include semi-literate farmers. The objectives of this research were to design web-based Geographical Information System decision support system data model for paddy precision farming (Web Paddy GIS) and to develop and implement the web-based GIS decision support system for paddy precision farming using open source software. This new system has been developed to function on Windows and Linux platforms. User satisfaction tests were conducted concerning website acceptability and performance testing were made during this research. The research demonstrates that Web Paddy GIS can successfully run on both platforms. However, the Linux platform has proven to be superior to Windows, based on factors such as CPU usage and speed. The system was implemented for an area in Selangor, Malaysia. This research presents a novel contribution addressing web-based precision farming for the semi-literate paddy farming community of a developing country. The development of a Web Paddy GIS is very useful for paddy farmers, farm managers, decision makers and researchers.